THE CONCEPT OF REWRITING, TYPES AND ITS DISLPAYS IN THE DIGITAL JOURRNALISM - Sultonova, Sayyora Ulugbekovna; Ikramova, S.A (Innovative Development in Educational Activities, 2023)
This article discusses the concept of rewriting, its types, distinctive features, its place in digital journalism today and how it ranks in the competition in the field of journalism.